A composite robust reactive control strategy for quadruped robot under external push disturbance. (May 2021) - Zhu, Xiaolu; Wan, Jinxiao; Zhou, Chuan; Xu, Wei
Abstract: In order to solve the walking stability problem of quadruped robot under lateral disturbance, a robust stabilization reactive control strategy based on capture point stability theory is proposed. This novel control strategy consists of an active adaptive stepping control strategy at the upper planning layer and a joint disturbance rejection controller based on virtual model control at the bottom layer. The adaptive stepping control strategy is based on the capture point stability theory, which determines the stable stepping point of the robot under the action of external disturbance according to the speed and attitude of the body, and the joint disturbance rejection controller at bottom layer realizes the stable torque control of the robot and adjusts the attitude of the body through the virtual model controller. Finally, the effectiveness of the designed composite control strategy is verified by co-simulation of Simulink and ADAMS. Simulation results show that the robot with the proposed composite reactive control strategy is able to cope with large external disturbance and recover to be stable from external force disturbance.